Inverse Association Between HDL (High-Density Lipoprotein) Cholesterol and Stroke Risk Among Patients With Type 2 Diabetes Mellitus. Issue 2 (February 2019) - Shen, Yun; Shi, Lizheng; Nauman, Elizabeth; Katzmarzyk, Peter T.; Price-Haywood, Eboni G.; Bazzano, Alessandra N.; Nigam, Somesh; Hu, Gang
Abstract : Background and Purpose—: Few studies have assessed the association of HDL (high-density lipoprotein) cholesterol with stroke risk among patients with type 2 diabetes mellitus. We aimed to investigate the association of HDL cholesterol with total and type-specific stroke risk in patients with type 2 diabetes mellitus. Methods—: We performed a retrospective cohort study of 27 113 blacks and 40 431 whites with type 2 diabetes mellitus. Cox proportional hazards regression models were used to estimate the association of different levels of HDL cholesterol with stroke risk. Results—: During a mean follow-up period of 3.0 years, 8496 patients developed stroke (8048 ischemic and 448 hemorrhagic). Multivariable-adjusted hazard ratios across levels of HDL at baseline (<30 [reference group], 30–39.9, 40–49.9, 50–59.9, 60–69.9, 70–79.9, and ≥80 mg/dL) were 1.00, 0.86, 0.77, 0.71, 0.71, 0.77, and 0.69 ( P trend <0.001) for total stroke, 1.00, 0.89, 0.82, 0.75, 0.78, 0.76, and 0.75 ( P trend <0.001) for ischemic stroke, and 1.00, 0.89, 0.69, 0.66, 0.47, and 0.94 ( P trend =0.021) for hemorrhagic stroke, respectively. When we used an updated mean value of HDL cholesterol, the inverse association of HDL cholesterol with stroke risk did not change. This inverse association was consistent among patients of different ages, races, sexes, body mass index, hemoglobin A1c levels, never and past or current smokers, and patients with and without using glucose-lowering, cholesterol-lowering, or antihypertensive agents. Conclusions—: The present study found consistent inverse associations between HDL cholesterol and the risk of total, ischemic and hemorrhagic stroke among patients with type 2 diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.